Obesity and recurrent urinary tract infections in premenopausal women: a retrospective study - William Nseir; Raymond Farah; Mahmud Mahamid; Helal Sayed-Ahmad; Julnar Mograbi; Mohamed Taha; Suheil Artul (International Journal of Infectious Diseases, 2015)
Objectives: Studies on the association between obesity and the risk of urinary tract infection (UTI) show inconsistent results. The aim of this study was to determine whether there is any association between obesity and recurrent UTIs (RUTIs) among premenopausal women. Methods: A retrospective case–control study was conducted in the outpatient clinics of the internal medicine departments of three hospitals. All consecutive non-pregnant premenopausal women aged 20–55 years, who presented with RUTIs over a 2-year period, were included; these women were compared to randomly selected women from the same outpatient clinics who had no history of RUTI and were age-matched ±5 years. RUTI was defined as a symptomatic UTI that followed the resolution of a previous UTI, or three or more symptomatic episodes over a 12-month period. Results: Six hundred and ninety-one premenopausal women with UTI were evaluated during the study period. A total 122 of 162 subjects with RUTIs were included in this study and compared to 122 control cases without a history of RUTI. The overall prevalence of RUTIs among the premenopausal women with UTI was 23.4% (162/691). Approximately half of those with RUTIs were obese. The mean age of women with RUTIs was 43.8 ± 9 vs. 40 ± 10 years among the controls (p = 0.839). The mean body mass index of women with RUTIs was significantly higher than that of controls: 35 ± 4 vs. 26 ± 3 kg/m2 (p < 0.001). Multivariate regression analysis showed that obesity was associated with RUTIs in premenopausal women (odds ratio 4.00, 95% confidence interval 3.2–4.61; p = 0.001). Conclusions: Obesity was found to be associated with RUTIs in premenopausal women.